Organizational support and job crafting with the new math teachers’ well-being: The mediating effect of basic psychological needs - Wang, Limei; Peng, Fuqiang; Song, Naiqing (Frontiers in Psychology, 2022)
Enhancement of the teacher well-being level has grown into a general, pressing problem to be solved in the domain of education worldwide. Based on the theoretical perspective of the multi-level dynamically formed mechanical model of occupational well-being, this study initially constructed a mechanism model with the occupational well-being role of organizational support, job crafting, and the occupational well-being of new math teachers at primary and junior high schools, and conducted empirical research using structural equation modeling. The study found out that organizational support, job crafting and basic psychological needs have prominent and positive effects on the occupational well-being of the new math teachers in primary up to junior high schools. It also argues that basic psychological needs may mediate the correlation between organizational support, job crafting, and the occupational well-being of the new math teachers. To sum up, the study findings reveal the mechanisms of the role in organizational support and job crafting on the occupational well-being of new primary up to junior high school math teachers. Also, the findings may be conducive to extending the research on the factors that influence the teacher well-being, notably fostering the study on that in the math teachers in the primary up to junior high schools of China.